Application of abrupt cut-off models in the analysis of the capacitance spectra of conjugated polymer devices - Reis, F. T.; Santos, L. F. [UNESP]; Bianchi, R. F.; Cunha, H. N.; Mencaraglia, D.; Faria, R. M. (Springer, 2009)
In this paper, a detailed study of the capacitance spectra obtained from Au/doped-polyaniline/Al structures in the frequency domain (0.05 Hz-10 MHz), and at different temperatures (150-340 K) is carried out. The capacitance spectra behavior in semiconductors can be appropriately described by using abrupt cut-off models, since they assume that the electronic gap states that can follow the ac modulation have response times varying rapidly with a certain abscissa, which is dependent on both temperature and frequency. Two models based on the abrupt cut-off concept, formerly developed to describe inorganic semiconductor devices, have been used to analyze the capacitance spectra of devices based on doped polyaniline (PANI), which is a well-known polymeric semiconductor with innumerous potential technological applications. The application of these models allowed the determination of significant parameters, such as Debye length (approximate to 20 nm), position of bulk Fermi level (approximate to 320 meV) and associated density of states (approximate to 2x10(18) eV(-1) cm(-3)), width of the space charge region (approximate to 70 nm), built-in potential (approximate to 780 meV), and the gap states' distribution.